2016
DOI: 10.1186/s12912-016-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Thai Nurses’ experiences of post-operative pain assessment and its’ influence on pain management decisions

Abstract: BackgroundWhile many studies have addressed various issues with regards to pain management, there is limited knowledge about how nurses assess pain in surgical wards. This study aimed to describe Thai nurses’ experiences of pain assessment in a surgical ward.MethodsA cross-sectional explorative study was conducted. Participants were selected through theoretical sampling. Data was collected through interviews with twelve registered nurses working in surgical wards. Qualitative content analysis guided the analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 23 publications
2
36
0
4
Order By: Relevance
“…They have added to the policies of all hospitals the recommendation that healthcare providers should assess pain as the fifth vital sign. In practice, the nurses record a patient's level of pain every 4 hours (6 times per day) in a variety of methods (i.e., a verbal scale such as the Numeric Rating Scale (NRS), a graphic sheet record, and medical records) with all of the patients in the studied surgical ward [18]. …”
Section: Methodsmentioning
confidence: 99%
“…They have added to the policies of all hospitals the recommendation that healthcare providers should assess pain as the fifth vital sign. In practice, the nurses record a patient's level of pain every 4 hours (6 times per day) in a variety of methods (i.e., a verbal scale such as the Numeric Rating Scale (NRS), a graphic sheet record, and medical records) with all of the patients in the studied surgical ward [18]. …”
Section: Methodsmentioning
confidence: 99%
“…One of our previous studies regarding Thai Nurses’ experiences of postoperative pain assessment found that nurses were using the double/triple check system as well as many forms of evidence, such as documentation and pain records, to communicate with the care team. Furthermore, the nurses have used their own previous experiences to assess pain and interpret pain intensity (10). Previous studies have revealed that nurses were limited in their abilities to manage the patients’ pain due to a lack of education and skills in pain management (e.g., administration of sedation, nursing interventions) (11, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Ağrının subjektif bir veri olması, çocuğun yaşı, gelişimsel düzeyi, mizacı, sosyokültürel faktörler, geçmiş ağrı deneyimleri, çocuklarda ağrı ile ilgili yanılgılar, ağrı belirtilerinin ayırt edilememesi, doğru ağrı ölçme araçlarının kullanılmaması çocuklarda ağrı değerlendirilmesini güçleştirmektedir. (5,7) Çocuklarda ağrının değerlendirilmesi için bazı ölçme araçlarından yararlanılmaktadır. Çocuklarda ağrı şiddetini ölçmek için kullanılacak araçların seçimi, çocuğun yaşı, genel durumu, ağrıyı tanıma düzeyi dikkate alınarak yapılmalıdır.…”
Section: • Researchunclassified
“…Çocuklarda postoperatif dönem ağrı değerlendirmesine yönelik yapılan çalışmalarda hemşirelerin çoğu zaman kanıta dayalı ölçekleri kullanmadığı görülmektedir. (4,5,10,14) Çocuk hemşirelerinin çoğunun daha çok kendi deneyimleri ya da hasta ifadeleri doğrultusunda ağrıyı değerlendirdiği bildirilmektedir. (5,10,11) Çocuk hemşirelerinin ağrı değerlendirmesine yönelik tutum ve davranışlarının incelendiği bir çalışmada, hemşirelerin postoperatif ağrıyı değerlendirirken ölçek kullanma oranlarının düşük olduğu, bu oranın özellikle 5 yaşın altındaki çocukların ağrısının değerlendirilmesinde daha da düşük olduğu belirtilmektedir.…”
Section: • Researchunclassified